Assessment of obesity and classification of patients: historical perspectives and current practice - Bray, George (Henry Stewart Talks, 2007)
Obesity is not a new problem, Palaeolithic times: Venus of Willendorf, Neolithic times: Venus of Catalhoyuk, MesoAmerican times: Mayan figurine, Historical times to 1500AD: Mesopotamian, Egyptian, Chinese and Tibetan, Indian and Greco-Roman, Modern times: modern themes, Not all obesities are the same: classifications, Body Mass Index and risk to health, Evaluation of obesity: clinical history, clinical classification, vital signs and laboratory measures, Genetic causes of obesity, Hypothalmic obesity, Dietary factors, Physical inactivity